Unusual Cause of Multiple Cranial Nerve Palsy - Mahbub, Md Shahriar; Al Faruq, Abdullah; Khan, Mohammad Ashik Imran; Ahasan, HAM Nazmul (Journal of Medicine, 2011)
DOI: 10.3329/jom.v12i1.6941 J Medicine 2011; 12 : 96